Primary Carcinoma in Ectoopic Thyroid - Rashid, Abdur; Khan, Arif Raza; Yousaf, Naveed; Ullah, Niamat (Journal of Postgraduate Medical Institute, 2011)
Ectopic thyroid is rare, and primary carcinoma in ectopic thyroid is even more rare. We present a case of papillary carcinoma in ectopic thyroid in a lady age 50 years who presented with a right sided neck mass.